Dari Pekarangan Ke Ketahanan Pangan: Pemberdayaan Kwt Melalui Bantuan Benih Dan Alat Pengolahan Pangan Lokal (Studi Kasus Di Kabupaten Indragiri Hulu) - Anggelia Valencia; Nur Hidayah; Heriyanto Putra; Sulaiman Zuhd (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
Food security is a global issue that plays a crucial role in achieving food self-sufficiency and poverty reduction. At the national level, Indonesia emphasizes community empowerment, particularly women’s participation, as a key strategy for strengthening sustainable food security through the utilization of local resources. One of its practical implementations is the empowerment of Kelompok Wanita Tani (Women Farmers Group/KWT) in food cultivation and processing activities. This study aims to analyze the impact of seed assistance and food processing technology support on improving household food security in Indragiri Hulu Regency, Riau Province. The research employs a descriptive qualitative approach using secondary data from the Food Security Agency of Indragiri Hulu Regency (2025) and national literature indexed by SINTA. The findings reveal that seed and food processing equipment assistance programs contribute to increasing food consumption diversification and strengthening household economies, particularly in priority areas for stunting reduction. However, program sustainability remains suboptimal due to the lack of monitoring systems, technical assistance, and market access for processed products. Therefore, this study recommends integrating empowerment programs with digital monitoring systems, strengthening KWT institutions, and enhancing local policy support to build sustainable household-based food self-sufficiency.